Effect of limited jaw motion on ankylosis of the temporomandibular joint in sheep - H. Miyamoto, K. Kurita,* N. Ogi, J.-I. Ishimaru, A.N. Goss (Blackwell Synergy, 2000)
Ankylosis of the temporomandibular joint (TMJ) causes functional and aesthetic problem as well as difficulties with feeding and oral hygiene.